STUDENTS’ PERCEPTIONS OF THE CONSTRUCTIVIST INSTRUCTIONAL METHODS IN A TEACHING AND LEARNING COURSE - Meri Fuji Siahaan (International Journal of Pedagogy and Teacher Education, 2017)
Constructivism is defined as building one’s own understanding. Constructivist instructional method requires that teacher should not be the one who informs but who facilitates the students learning. The purpose of this study is to obtain the students’ perceptions on the implementation of constructivist instructional methods in Teaching and Learning course. A survey research methodology was used with first semester students who were taking teaching and learning course as the subjects of this study. Methods of collecting data were questionnaires with open ended questions, deep interview and documentation. A qualitative analysis technique was performed on data from the survey instrument and the interview to answer 4 research questions. A descriptive analysis technique was performed on data to answer 1 research question from the survey instrument and documents. The data analysis revealed that constructivism instructional methods were clearly experienced when they were required to answer a lot of probing questions, had discussion in the classroom, had Facebook online discussions with clear guidance to do so, created ted talks and debating.The study implies that the constructivist instructional methods experienced by the students in the class help them to better understand the constructivism theory and its implications.